2007
DOI: 10.1111/j.1600-0846.2007.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin phosphocreatine

Abstract: Background/purpose: The skin has the unique ability to survive ischemia associated with skin grafts, flaps and hair transplantation procedures. Spectroscopic data later confirmed by chromatography, immunohistochemistry and molecular biology techniques identified the presence of large quantities of phosphocreatine in human skin. Phosphocreatine molecules regenerate ATP cellular reserves during ischemia. This reaction is mediated by creatine phosphokinase enzymes that were also isolated and studied in normal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Our observation of increased PCr (Table I) in burn tissue provides support for the notion that PCr is increased in response to burn injury (40). Both the PCr and creatine increases that we observed are probably due to an elevated activity of creatine phosphokinase enzyme (CPK) which mediates the conversion of ATP to PCr and PCr’s breakdown to creatine and phosphorous.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our observation of increased PCr (Table I) in burn tissue provides support for the notion that PCr is increased in response to burn injury (40). Both the PCr and creatine increases that we observed are probably due to an elevated activity of creatine phosphokinase enzyme (CPK) which mediates the conversion of ATP to PCr and PCr’s breakdown to creatine and phosphorous.…”
Section: Discussionsupporting
confidence: 80%
“…Both the PCr and creatine increases that we observed are probably due to an elevated activity of creatine phosphokinase enzyme (CPK) which mediates the conversion of ATP to PCr and PCr’s breakdown to creatine and phosphorous. Indeed, CPK is elevated in burn victims, probably due to keratinocyte necrosis and leakage of CPK into circulation (40). …”
Section: Discussionmentioning
confidence: 99%
“…In the past 10 years, a number of research groups around the world confirmed our results by spectroscopic, chromatographic and, most recently, by molecular biology and immunohistochemical methods and this information was recently reviewed in a published editorial (6–8). The skin has a metabolically very active and functional PCR/CPK system that, among other things, explains the unique ability of cutaneous tissue to withstand ischemia associated with skin flaps, grafts and hair transplantation procedures; it also plays an important role in protecting skin from ultraviolet radiation (6–8). Unfortunately, only very few dermatologists and other investigators are even aware of the existence of skin CPK/PCR systems; as these authors and Caux discussed, over 10 years ago, our understanding of skin CPK/PCR system is at best extremely limited (9, 10).…”
supporting
confidence: 58%
“…The present authors were the first to detect PCR in human skin in vivo by 31 P MRS (3), to measure skin PCR molecular concentration by high-pressure liquid chromatography (4) and measure cytosol CPK level in normal human, murine, human psoriatic skin and in a variety of benign and malignant human skin lesions (5). In the past 10 years, a number of research groups around the world confirmed our results by spectroscopic, chromatographic and, most recently, by molecular biology and immunohistochemical methods and this information was recently reviewed in a published editorial (6)(7)(8). The skin has a metabolically very active and functional PCR/CPK system that, among other things, explains the unique ability of cutaneous tissue to withstand ischemia associated with skin flaps, grafts and hair transplantation procedures; it also plays an important role in protecting skin from ultraviolet radiation (6)(7)(8).…”
mentioning
confidence: 66%
“…In epithelial cells of the intestine (Sistermans et al 1995a) CK may be involved in food absorption and transport, as well as cell renewal. In skin, BB-CK and umtCK have been localized in the keratinocytes of the highly proliferative suprabasal layer of the epidermis, as well as in the hair follicles and sebaceous glands (Schlattner et al 2002), indicating a function of the CK/PCr system for normal skin function (Zemtsov 2007), proliferation and hair growth (Schlattner et al 2002). During wound healing, CK isoforms were highly upregulated indicating a function of CK and Cr (Schlattner et al 2002).…”
Section: The Ck/pcr System For Temporal and Spatial Buffering And Regmentioning
confidence: 99%